Corrigendum to "Effect of a Nutrition Diet on Health Status of Physically Challenged Students at Ade Okubanjo Institute for the Blind, Ijebu-Igbo" [SBCH 2023; 7(1): 973-979] - Titilayo Monsurat Musa; Adekola Ridwan Ademola; Adewale Olugbemiga Adeleye; Khadijat Oluwapelumi Popoola (Journal of Social Behavior and Community Health)
The mistake made in Article 3 is that the affiliation of the first Author is "Department of Human Kinetics and Health Education, Olabisi Onabanjo University, Ago – Iwoye, Negeria" and the correct affiliation is "Department of Education Foundation and Counseling, Olabisi Onabanjo University, Ago – Iwoye, Negeria". The publisher apologizes on behalf of the author for this error. The online version of the article was updated on 2023 and can be viewed at https://sbrh.ssu.ac.ir/article-1-208-en.html